Isotope ratios in Zechstein carbonates - Andreas Below (PANGAEA, 1992)
Ten exploration wells penetrating the Zechstein from the Weser-Ems-Region (North- Western Gerrnany) were investigated in respect to the facies, the petrographic features and isotopic composition of the Ca2-carbonates. The carbonate deposits of the ten wells are located at the southern marginal platform of the Gennan Zechstein Basin. The thickness of the Ca2- carbonates varies between 40 and 220 m. Sedimentation of the Ca2 started with the transgression of the Zechstein sea over the sulfates of the Al. The inundation of the Al-platform is characterised by the growth of thick ooid- layers. These layers are divided into two cycles, witch can be characterised as two shallowing upward-cycles with inter- to subtidal sediments at the end of the cycles. The sediment structures and the particle composition (ooids, grapestones, peloidal grains and bioclasts) of the Ca2-carbonates allows the differentiation in high energy or protected ooidsands and less agitated tidal-flat sediments. ff ...
Supplement to: Below, A (1992): Fazies- und geochemische Diagenesestudie im Zechstein 2-Karbonat (Ca2) Nordwestdeutschlands. Berichte - Reports, Geologisch-Paläontologisches Institut und Museum, Christian-Albrechts-Universität, Kiel, 60, 147 pp, https://doi.org/10.2312/reports-gpi.1992.60